Dynamic Alterations and the Affecting Attributes of the Unbalanced Economic Development in the Basin of the Yellow River: Analysis Utilizing Population-Weighted Coefficient of Variation - Ziqiang Zhao (Journal of Mathematics)
This paper employs a method called the population-weighted coefficient of variation (PWCV) to investigate the dynamic changes related to the imbalanced economic progression in the Yellow River Basin (YRB) between 2010 and 2020, and also analyzes the affecting attributes that are related to industry-specific and the spatial property of this change through the double decomposition of the PWCV method. The imbalanced economic progression in the YRB that tends to decline generally was found. The basin of the Yellow River, with three constituent regions, namely upper, middle, and lower streams of it, experiencing an imbalanced development has roots in the condition of the imbalanced economic progression in the YRB. However, since 2018, the imbalance ratio between regions has expanded. When the industrial decomposition is under consideration, the YRB experiences imbalanced economic development due to the dissimilarity between the industrial implementations, called the secondary and tertiary. Before 2018, the imbalance caused by the difference in the secondary industry accounted for more than 50%, while the imbalance led by the difference in the tertiary industry exceeded the imbalance caused by the secondary industry after 2018.